1995
DOI: 10.3758/bf03200922
|View full text |Cite
|
Sign up to set email alerts
|

Why is 9+7 harder than 2+3? Strength and interference as explanations of the problem-size effect

Abstract: In four experiments, the problem-size effect was investigated, using an alphabet-arithmetic task in which subjects verified such problems as A + 2 =C. Problem size was manipulated by varying the magnitude ofthe digit addend (e.g., A + 2, A + 3, and A + 4). The frequency and similarity of problems was also manipulated to determine the contribution of strength and interference, respectively. Experiment I manipulated frequency at low levels of practice and found that strength could account for the problem-size ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 26 publications
11
83
0
Order By: Relevance
“…In the linguistic domain, dramatic differences in word frequency (from about 3000 to 60 per million) result in rather small differences in RTs (i.e., 15 ms in a lexical decision task, Ferrand et al, 2011), whereas the observed difference in RTs between probably very frequent additions such as 2 + 1 and 2 + 4 was higher than 90 ms. Finally, the size effect we observed does not seem to result from interferences in a memory network as Zbrodoff, 1995) suggested. An index we called Overlap reflecting the number of problems sharing the same answer as the problem under study was the worst among the eight predictors of RTs that we entered in our analyses (r = .10, n.s.).…”
Section: Recent Evidence For a Problem-size Effect Due To Counting Stmentioning
confidence: 58%
See 1 more Smart Citation
“…In the linguistic domain, dramatic differences in word frequency (from about 3000 to 60 per million) result in rather small differences in RTs (i.e., 15 ms in a lexical decision task, Ferrand et al, 2011), whereas the observed difference in RTs between probably very frequent additions such as 2 + 1 and 2 + 4 was higher than 90 ms. Finally, the size effect we observed does not seem to result from interferences in a memory network as Zbrodoff, 1995) suggested. An index we called Overlap reflecting the number of problems sharing the same answer as the problem under study was the worst among the eight predictors of RTs that we entered in our analyses (r = .10, n.s.).…”
Section: Recent Evidence For a Problem-size Effect Due To Counting Stmentioning
confidence: 58%
“…Assuming a process of spreading activation through the memory network, the time needed to reach a given intersection (i.e., the correct sum) would be proportional to the area of the network to be traversed, hence the predictive power of the product of the two addends. Zbrodoff (1995) and Zbrodoff and Logan (2005) proposed a network interference model in which problem-answer associations take longer to retrieve for larger problems because they suffer from more interference created by overlap of their operands or answers.…”
Section: A Discordant Phenomenon: the Problem-size Effectmentioning
confidence: 99%
“…The problem-size eVect, which refers to slower and more error-prone performance on large problems (e.g., 8 £ 9) than on small problems (e.g., 2 £ 3), is one of the most robust eVects observed in mental-arithmetic research (Ashcraft 1992;ZbrodoV 1995). According to Campbell and Xue (2001), there are three strategy-related sources of the problem-size eVect in adults: less frequent retrieval use for large than for small problems, lower retrieval eYciency for large than for small problems, and lower procedural eYciency for large than for small problems.…”
Section: Evects Of Problem Size On Arithmetic Strategy Usementioning
confidence: 99%
“…LeFevre et al's (1996) college subjects frequently reported using a counting strategy. The different status of the N+1 problems compared to problems with addends larger than 1 has implicitly been assumed by researchers who did not include these items in testing a model of arithmetical fact retrieval (e.g., Campbell, 1994Campbell, , 1995Zbrodoff, 1995).…”
Section: -Problemsmentioning
confidence: 99%